Shun Li and the poet [videorecording (DVD)] - Segre, Andrea, 1976-; Zhao, Tao, 1978-; Šerbedžija, Rade, 1946-; Paolini, Marco (Film Movement series., 2013)
A study of the friendship between a Chinese woman and a fisherman who came to Italy from Yugoslavia many years ago, who live in a small city-island in the Venetian lagoon.